Reference values for amino acids and acylcarnitines in peripheral blood in Quarter horses and American Miniature horses - Rodríguez Sánchez, Irám Pablo; Treviño Alvarado, Víctor Manuel; Torres Sepúlveda, María del Rosario; López Saldaña, Liliana Aracely; Ponce García, Gustavo; López Uriarte, Graciela Areli; Ruiz Herrera, María del Consuelo; Zamora Ávila, Diana Elisa; Villarreal Pérez, Jesús Zacarías; Dávalos Aranda, Guillermo; Martínez de Villarreal, Laura Elia (BioMed Central, 2015)
Background: Free amino acids and acylcarnitines circulating in the blood can be used for diagnosis for metabolic illness and imbalances. To date, the normal reference ranges of amino acids and acylcarnitines in horse peripheral blood have not been established. In this study, the concentrations of 12 amino acids and 26 acylcarnitines were deter‑mined by tandem mass spectrometry in complete blood from 100 healthy horses (50 Quarter horses (QH) [23 males and 27 females] and 50 American Miniature horses (AMH) [15 males and 35 females]) with no signs of metabolic disease. The means and standard deviations were determined and data statistically analyzed. Findings: Concentrations of short, medium, and long chain acylcarnitines were significantly higher in male AMH than in male QH. The concentrations of the amino acids alanine, arginine, glycine, proline (glycogenic), and leucine (ketogenic) were higher in the QH than in the AMH. Female AMH had higher concentrations of propionylcarnitine, leucine, proline, arginine, and ornithine than female QH. Conclusions: Normal reference ranges of amino acids and acylcarnitines were established for AMH and QH. Signifi‑ cant differences were found in concentration of these compounds between breeds and gender.